Robust vibration control of ﬂexible panel:modeling and simulation - Banu, Aalya; Abdul Muthalif, Asan Gani (Emerald Group Publishing Ltd., 2017)
Purpose – This paper aims to develop a robust controller to control vibration of a thin plate attached with two piezoelectric patches in the presence of uncertainties in the mass of the plate. The main goal of this study is to tackle dynamic perturbation that could lead to modelling error in ﬂexible structures. The controller is designed to suppress ﬁrst and second modal vibrations. Design/methodology/approach – Out of various robust control strategies, -synthesiscontrollerdesignalgorithmhasbeenusedforactive vibration control of a simply supported thin place excited and actuated using two piezoelectric patches. Parametric uncertainty in the system is taken into account so that the robust system will be achieved by maximizing the complex stability radius of the closed-loop system. Effectiveness of the designed controller is validated through robust stability and performance analysis. Findings – Results obtained from numerical simulation indicate that implementation of the designed controller can effectively suppress the vibration of the system at the ﬁrst and second modal frequencies by 98.5 and 88.4 per cent, respectively, despite the presence of structural uncertainties. The designed controller has also shown satisfactory results in terms of robustness and performance. Originality/value – Although vibration control in designing any structural system has been an active topic for decades, Ordinary ﬁxed controllers designed based on nominal parameters do not take into account the uncertainties present in and around the system and hence lose their effectiveness when subjected to uncertainties. This paper fulﬁlls an identiﬁed need to design a robust control system that accommodates uncertainties.